Peran Penting Psikologis terhadap Peserta Didik SD Melalui Pembelajaran Tematik-Terpadu - Hariyani, Yunita (JURNAL EDURELIGIA, 2018)
This study aims to determine the important role of psychology in elementary school students through thematic-integrated learning. The method used by library research. Data collection uses documentation and data analysis with descriptive analysis. The results of the study indicate that learning using themes in linking several subjects can provide meaningful experiences to students. Likewise seen from the social aspect, students in elementary school began to form new bonds with peers and began to be able to adjust themselves to the attitude of cooperation. While psychologically also has begun to learn to control and control his emotional expression.